2019
DOI: 10.3390/polym11050835
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Transformation of One-Year-Old Plants During Anaerobic Digestion (AD)

Abstract: The aim of the research is to identify the changes which occur in lignin from miscanthus and sorghum, one of the main biomass components, as a result of an anaerobic digestion (AD) process. The percentage content and structure of lignin before and after the fermentation process were analysed using biomass harvested in two growing periods—before and after vegetation. It was shown that plants at different developmental stages differ in lignin content. During plant growth, the lignin structure also changes—the sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…Similarly, it was found that AD degradation of birch hydrolysis lignin drastically reduced the S/G ratio of the material, indicating preferential degradation of syringyl units [44]. Positive correlations between S/G ratio and AD performance in degradation of lignocellulosic materials have generally been reported, for example, in Populus biomass using C. thermocellum [45], in AD of herbaceous material [46], as well as in the present study. However, in a study on non-pretreated Salix, evaluating correlations between methane potentials and rates and FT-IR spectral features [38], some G lignin-assigned wavenumbers were positively correlated with both potentials and rates, although this finding was confounded by positive correlations between these wavenumbers and carbohydrate content.…”
Section: Influence Of Lignin Compositionsupporting
confidence: 86%
“…Similarly, it was found that AD degradation of birch hydrolysis lignin drastically reduced the S/G ratio of the material, indicating preferential degradation of syringyl units [44]. Positive correlations between S/G ratio and AD performance in degradation of lignocellulosic materials have generally been reported, for example, in Populus biomass using C. thermocellum [45], in AD of herbaceous material [46], as well as in the present study. However, in a study on non-pretreated Salix, evaluating correlations between methane potentials and rates and FT-IR spectral features [38], some G lignin-assigned wavenumbers were positively correlated with both potentials and rates, although this finding was confounded by positive correlations between these wavenumbers and carbohydrate content.…”
Section: Influence Of Lignin Compositionsupporting
confidence: 86%
“…Much less desirable raw materials for biogas production are wastes with a high lignin content. Lignocellulosic biomass contains natural polymers such as cellulose, hemicellulose, and lignin [ 1 , 2 , 3 ]. Cellulose and hemicellulose as carbohydrates suitable as feedstock are fermentable after hydrolysis for bioenergy production.…”
Section: Introductionmentioning
confidence: 99%
“…Other results from batch degradation of plant main components showed that the biomethane potential of cellulose was higher than that of hemicellulose, but this latter was characterized by easier hydrolysis than the first one. On the contrary, lignin had proven to be difficult to digest [ 74 ], experiencing small changes in its native structure when extended digestion periods were applied, resulting in a simpler structure with fewer functional groups than those of the native lignin [ 75 ].…”
Section: The Effect Of Substrate Composition and Digestion Performmentioning
confidence: 99%